The Influence of The Board of Commissioners' Tenure on Firm Value With Sustainability Reporting Disclosure as an Intervening Variable - Ita Lestari; Risa Nurdzanah (Universitas Darwan Ali, 2025)
This study was conducted to analyze the relationship between the tenure of the board of commissioners and firm value, utilizing sustainability reporting disclosure as an intervening variable. The research focuses on manufacturing entities within the mining and chemical industry sectors listed on the Indonesia Stock Exchange throughout the 2020–2024 period. In this framework, the tenure of the board of commissioners serves as the independent variable, while firm value measured via the Tobin’s Q ratio acts as the dependent variable, with sustainability disclosure transparency across economic, environmental, and social dimensions functioning as the mediating variable. Through purposive sampling, a sample of 26 manufacturing companies was selected for a five-year observation period, and the collected data were analyzed using path analysis techniques with SPSS 25 software. The empirical findings reveal that the duration of the board of commissioners' tenure has no significant impact on either market value or the quality of sustainability disclosures; however, sustainability disclosure itself demonstrates a significant positive influence on firm value, despite not proving to function as a mediator in this model. This phenomenon suggests that market appreciation is driven more by transparency regarding sustainability issues than by board seniority, implying that these findings may serve as a reference for issuers, investors, and policymakers in Indonesia to strengthen sustainability reporting standards as a vital element of long-term responsible corporate governance.